HMRC's discretion: The application of the ultra vires rule and the legitimate expectation doctrine - Tracey Bowler (Institute for Fiscal Studies (IFS), 2014)
[Introduction] This is a discussion paper, written for the Tax Law Review Committee of the Institute for Fiscal Studies, considering the way in which the courts limit the exercise of discretion by HMRC, in particular by reference to the doctrine of legitimate expectation, and how this affects the interaction between taxpayers and the taxing authority. It is set against a background of increasing levels of discretionary power being given to HMRC and, as a result, increasing concern about the relationship between HMRC and taxpayers. The paper aims to promote discussion about the extent of HMRC's discretion in interpreting and applying the tax rules set out by Parliament and whether taxpayers' abilities to challenge the use of that discretion are sufficient. The paper identifies problems with the application of HMRC's discretionary powers and the ability of taxpayers to rely on the various forms of statements and guidance which HMRC are increasingly under pressure to provide, as well as considering the procedures for claiming reliance on statements. It also suggests some ways to improve the position and invites comments and debate of the issues.
Additional information: TLRC Discussion Paper No. 10.
Keywords: 330